Implementasi Peraturan Bupati Kabupaten Mahakam Ulu Nomor 30 Tahun 2017 Tentang Petunjuk Pelaksanaan Pemungutan Pajak Restoran Oleh Badan Pendapatan Daerah Kabupaten Mahakam Ulu - Helong, Katharina (Jurnal Paradigma, 2023)
This study aims to describe and analyze the implementation of the Regent's Regulation of Mahakam Ulu Regency Number 30 of 2017 concerning Guidelines for the Implementation of Restaurant Tax Collection by the Regional Revenue Agency of Mahakam Ulu Regency and the factors that hinder the implementation of the policy. This research is a descriptive study with a qualitative approach and analyzed using an interactive model. The results of the study indicate that in general, the implementation of restaurant tax collection based on Regent Regulation Number 30 of 2017 concerning Instructions for Implementing Restaurant Tax Collection in increasing Regional Original Income in Mahakam Ulu Regency has not gone well or as it should. It can be seen through the registration and tax reporting indicators that almost all taxpayers do not come to report their restaurant/food stall business taxes. This is due to several obstacles such as the lack of taxpayer compliance as a result of the lack of intensity of socialization of the benefits of paying taxes to the public and the absence of the use of information technology in restaurant tax services. Keywords: Implementation, Tax, Restaurant